Perceived Stress and Self-Prescribing Behavior: A Preliminary Cross-Sectional Study among Specialized Residency Training in Indonesia - Kusumastuti, Inke; Nurwanti, Ratri (HM Publisher, 2024)
Introduction: Challenges in specialist medical education in Indonesia can increase stress, but the expression of stress may be hampered or appear as physical complaints. The behavior of self-prescribing medication often occurs among specialist medical education participants to deal with stress-related complaints. This study aims to analyze the relationship between stress and self-prescribing behavior among specialist medical education participants in Indonesia. Methods: This cross-sectional study involved 39 respondents who completed an anonymous online survey. The perceived stress scale (PSS-10) was used to measure stress levels, and questions about medication self-prescribing behavior were asked. Multinomial logistic regression was used to analyze the relationship between PSS scores and self-prescribing behavior. Results: Most respondents (74.4%) had PSS scores higher than age and gender norms. Antibiotics were the most frequently self-prescribed medication (92.3%). No association was found between demographic characteristics, total PSS score, and self-prescribing behavior. Conclusion: The high level of stress in specialist medical education participants may not be directly correlated with self-prescribing behavior. This may be related to Asian culture where psychological distress tends to manifest as somatic complaints.